From posters to displaying: poster communication in Osijek in the early 20th century (Libellarium: journal for research in the field of information and related sciences, 2009)
There are many monographs, articles, chapters and exhibitions and their catalogues dedicated to Croatian posters from the early 20th century. Posters are evaluated as works of art, but received very little attention as an advertising medium. Their communication and advertising role in the specified time and place has not been investigated thoroughly. This paper does not investigate the relationship between the artistic and marketoriented aspects of posters, neither does it evaluate which and what type of posters deserve to be considered works of art. It focuses on how and where did people in the early 20th century used posters to inform themselves about new events and products. Posters are viewed only as a communicative and promotion medium, and the place where they were displayed as a sort of an information hub.The authors investigate the possibility of using two types of historical resources: city administration documents that regulated the displaying of posters and different pictures - like postcards, newspaper photos showing current events, posters and notice-boards or columns. The city of Osijek is selected as a case study for this approach. As the appropriation of posters is determined by their content, graphic design and place where they are displayed, the aim of the paper is to investigate the possible resources that can help us reconstruct the procedures and locations for poster displays. Following the methodology proposed by Robert Darnton, who listed five possible approaches to investigating different texts, and by Roger Chartier’s papers in which he stresses the importance of content appropriation, i.e. the subjectivity of readers, and not the de-contextualized content itself, the authors propose a step from posters to displaying them - or advertising - in public places in the city.Analyzing the above stated sources it can be established that there was a demand for the public advertising space in Osijek in the early 20th century. Advertising columns were covered in posters and served as ‘information centers’. It can be concluded that the efficiency of posters depended on their graphic design and the way they were displayed in the public space in the city, as most posters, especially the ones on cultural issues, did not rely as much on visual attractiveness or quick transfer of information, as they did on the continuity of the location where they were displayed. There was a huge demand for the advertising space, as the city administration had to draft statutes to regulate the displaying of posters. There were clients who rented the display rights for a certain time period. It can be concluded that there were many businesses and institutions that wanted or had to advertise their products, services or events, as well as the interested citizens who needed this information.The authors believe that the investigation of the communicative role of posters cannot rely only on the evaluation of the different aspects of posters themselves, but they had to be observed as communication media. The display or publishing mode also needs to be taken into consideration. Therefore, posters must be contextualized and analyzed in the public city space where they were displayed. Two historical resources that we used in this paper: city administration ordinances and visual records (postcards and photos), can be used as very useful to reconstruct the procedure and place for displaying posters.
Keywords: poster; poster displays; promotion; media; communication; Osijek; advertising columns; poster appropriation